Pengaruh Penggunaan Aplikasi Web Wordwall Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 5 Kota Tangerang Selatan - Noer Syafitri (Jurnal Pendidikan Islam, 2023)
This research was conducted to determine whether or not there is an influence of wordwall web applications on student learning outcomes in Islamic Religious Education subjects. This research was conducted at SMA Negeri 5 Kota Tangerang Selatan. Samples were taken using the Non-Probability Sampling technique, namely Purposive Sampling as many as 113 students. This research is quantitative with inferential statistical types: Validity Test, Reliability Test, Normality Test, Simple Linear Regression Test and Hypothesis Test. This calculation uses the SPSS application version 26. Data collection begins with the use of the wordwall web application during learning as a measure of learning outcomes after the material is presented in its entirety, then fills out a questionnaire related to wordwall web application variables and student learning outcomes variables via google form. The results of this study indicate that the calculation of Simple Linear Regression is 0.000 <0.05, the significance value is strong, if the significance value is <0.05, then the two variables influence each other. With a correlation of determination, namely 0.756, the interpretation obtained is a high correlation. Testing the H1 hypothesis is accepted, which means that the wordwall web application has a positively influences on student learning outcomes.